Metafora dalam puisi modernis Inggris “April Is The Cruellest Month”: Analisis semiotik - Kemala, Ajeng Ayu (Maliki Interdisciplinary Journal, 2024)
A literary work does not possess meaning or aesthetic value until the reader provides their own interpretation. English modernist poetry, which flourished during the early 20th century, marked a paradigm shift in the way poets viewed and interpreted the world, one example being "April Is The Cruellest Month" by T.S. Eliot. Against the backdrop of social change and the chaos following World War I, modernist poetry reflects the complexity of human experience through innovative language use and unconventional narrative structures. In analyzing how metaphors in English modernist poetry not only create visually rich imagery but also challenge readers to see reality from a different perspective, a qualitative approach reveals that, overall, this poetry employs semiotics to explore themes such as loss, despair, and the search for meaning in a fragmented and uncertain world. Each symbol and metaphor in the poetry serves as a sign that invites readers to interpret and seek deeper meaning from the text.